2014
DOI: 10.2147/ijn.s57930
|View full text |Cite
|
Sign up to set email alerts
|

Zinc oxide nanoparticles: a 90-day repeated-dose dermal toxicity study in rats

Abstract: Zinc oxide (ZnO) works as a long-lasting, broad-spectrum physical sunblock, and can prevent skin cancer, sunburn, and photoaging. Nanosized ZnO particles are used often in sunscreens due to consumer preference over larger sizes, which appear opaque when dermally applied. Although the US Food and Drug Administration approved the use of nanoparticles (NPs) in sunscreens in 1999, there are ongoing safety concerns. The aim of this study was to evaluate the subchronic toxicity of ZnO NPs after dermal application ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Although skin could be damaged by dermal exposure to NPs, the NPs ability to impair internal organs through penetrated NPs from the skin is extremely limited. Ryu et al (2014) observed dose-dependent inflammation of the skin at the application site in rats after exposure to ZnO NPs for 90 days. Nevertheless, no abnormal findings related to the effect of NPs in other internal organs, such as liver, kidneys and intestine were observed (Ryu et al, 2014).…”
Section: Toxicity Of Other Organsmentioning
confidence: 88%
“…Although skin could be damaged by dermal exposure to NPs, the NPs ability to impair internal organs through penetrated NPs from the skin is extremely limited. Ryu et al (2014) observed dose-dependent inflammation of the skin at the application site in rats after exposure to ZnO NPs for 90 days. Nevertheless, no abnormal findings related to the effect of NPs in other internal organs, such as liver, kidneys and intestine were observed (Ryu et al, 2014).…”
Section: Toxicity Of Other Organsmentioning
confidence: 88%
“…Hepatorenal toxicity due to high liver and kidney levels of p53, TNF-α and IL-6. Generation of oxidation stress as shown by low GSH but high thiobarbituric acid reactive substance (TBARS) levels [186] [191] Dermal exposure 75, 180 and 360 mg/kg for 28 d ZnO NPs penetrate into the dermis and reduce its collagen content [192] Intraperitoneal injection Single dose of 2500 mg/kg. Monitoring toxic effects after injection for 24, 48 and 72 h Accumulation in liver, spleen, lung, kidney and heart [193] Intraperitoneal injection 1, 10 and 100 mg/kg.…”
Section: In Vivo Animal Modelmentioning
confidence: 99%
“…Ryu et al conducted a repeated dermal exposure of citrate coated ZnO NPs (20 nm; 250, 500 and 1000 mg/kg bw) to Sprague Dawley rats for 90 days. Transient, dose-dependent irritation of the clipped skin at the application sites was observed [ 191 ]. However, no obvious adverse effects of ZnO NPs up to 1000 mg/kg bw applied dermally to the rats.…”
Section: In Vivo Animal Modelmentioning
confidence: 99%
“…In recent years, nanosized forms of ZnO and TiO 2 have been optimized to be more transparent, less viscous (more spreadable) [109], and easier to blend, while maintaining their potency against UV irradiation [110]. However, their toxicity profiles need to be assessed since smaller sized particles will likely have different chemical, optical, magnetic, and structural properties [111].…”
Section: Topical Applications Of Nanoparticlesmentioning
confidence: 99%